Kako z obštudijskimi dejavnostmi do boljših kariernih priložnosti? - Japelj, Nuša (Farmacevtski vestnik, 2020)
Each student enrolled in Faculty of Pharmacy, University of Ljubljana can have a very active and interesting extracurricular experience as a participant or an organiser of various events. Students of the Faculty are organised in student associations through which we organise different local and international events, such as International Pharmaceutical Summer Camp, educational evenings, Patient Counselling Events, pharmaceutical parties and we publish a newsletter Spatula. We are especially proud of organising large international congresses that established our associations as respected in Europe and the World. Through our associations, students develop soft skills, gain new knowledge and experience, meet new people and forge new long-lasting friendships.
Keywords: Farmacija; Študenti